Exploring ethical frontiers: Moral dimensions in the tapestry of contemporary Indonesian literature - Ali Imron Al-Ma'ruf; Zainal Arifin; Farida Nugrahani (Studies in English Language and Education, 2024)
Literary works have the potential to enhance a readers internal reservoir of life values without being dismissive. Contemporary Indonesian literature specifically imparts moral messages to its readers. This study aims to explain the moral dimensions present in this literature, utilizing descriptive qualitative methods. Purposive sampling was employed for data collection, covering words, sentences, and discourse representing morals from contemporary Indonesian literary works. This research relies on a literature study for data collection, employing the dialectical method for analysis by oscillating between literary texts and social reality. The findings reveal diverse moral dimensions within contemporary Indonesian literature, each contributing significantly to enriching the readers inner repertoire. These moral dimensions include (1) transcendental: aligning oneself to God, (2) struggle against evil (jihad fii sabiilillah), (3) nationalism, (4) getting closer to God (transcendental value), (5) gender equality as respect for women, (6) upholding the dignity of women, (7) remembering God (dhikr), (8) low morale leading to corruption, (9) upholding religion above worldliness, and (10) religious idea: life is a pseudo-game. The studys implications suggest that contemporary Indonesian literature serves as a significant source for fostering moral values, contributing to readers inner development by highlighting themes such as spirituality, societal responsibility, and ethical conduct. This insight can inform educational and cultural initiatives to promote moral awareness and consciousness.